2022
DOI: 10.1126/sciadv.abq2047
|View full text |Cite
|
Sign up to set email alerts
|

Endoreplication mediates cell size control via mechanochemical signaling from cell wall

Abstract: Endoreplication is an evolutionarily conserved mechanism for increasing nuclear DNA content (ploidy). Ploidy frequently scales with final cell and organ size, suggesting a key role for endoreplication in these processes. However, exceptions exist, and, consequently, the endoreplication-size nexus remains enigmatic. Here, we show that prolonged tissue folding at the apical hook in Arabidopsis requires endoreplication asymmetry under the control of an auxin gradient. We identify a molecular pathway linking endor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It is also discussed that P. brassicae induces wall stress and cell expansion in its host (Badstöber, Ciaghi, et al, 2020), resulting in alterations of the cell cycle (Olszak et al, 2019). Endoreduplication is linked to cell growth and cell wall remodelling (Bhosale et al, 2019; Bhosale & Vissenberg, 2023; Ma et al, 2022), so the growth of the parasite could indirectly induce the host to undergo additional rounds of endocycling, with the resulting energy sink providing nutrients for the Phytomyxea. The causal relationships between endoreduplication, cell growth, and cell wall modifications are not completely understood yet and more studies are needed to identify whether P. brassicae induces endoreduplication via mechanical pressure causing cell expansion, or whether cell expansion is a consequence of an effector mediated induction of endoreduplication.…”
Section: Discussionmentioning
confidence: 99%
“…It is also discussed that P. brassicae induces wall stress and cell expansion in its host (Badstöber, Ciaghi, et al, 2020), resulting in alterations of the cell cycle (Olszak et al, 2019). Endoreduplication is linked to cell growth and cell wall remodelling (Bhosale et al, 2019; Bhosale & Vissenberg, 2023; Ma et al, 2022), so the growth of the parasite could indirectly induce the host to undergo additional rounds of endocycling, with the resulting energy sink providing nutrients for the Phytomyxea. The causal relationships between endoreduplication, cell growth, and cell wall modifications are not completely understood yet and more studies are needed to identify whether P. brassicae induces endoreduplication via mechanical pressure causing cell expansion, or whether cell expansion is a consequence of an effector mediated induction of endoreduplication.…”
Section: Discussionmentioning
confidence: 99%
“…Such attenuation of cell-cycle progression together with decreased transcript levels of mitotic cyclins were shown to occur in budding yeast and Arabidopsis (Negishi et al, 2016; Gigli-Bisceglia et al, 2018) following the activation of a cell-wall integrity (CWI) checkpoint. More recently, Ma and colleagues proposed a scenario where the CWI kinase THESEUS1 (THE1), with a related gene being induced in infected root hairs (Breakspear et al, 2014; Liu et al, 2019a), triggers cell wall stiffening as a response to endoreduplication attenuation (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other receptors are also likely to be involved, such as THESEUS1 (THE1), because of their ability to sense cell‐wall integrity (Hématy et al ., 2007). Recent studies have found that endoreplication can control cell size via mechanochemical signalling from cell wall during the formation of apical hooks (Ma et al ., 2022). Endoreplication reduction enhances pectin methylesterification, leading to cell wall stiffening.…”
Section: Possible Pathways Influencing Cmt Behavioursmentioning
confidence: 99%
“…Endoreplication reduction enhances pectin methylesterification, leading to cell wall stiffening. THE1 is sensitive to the increase in cell wall stiffness and negatively regulates cell elongation (Ma et al ., 2022).…”
Section: Possible Pathways Influencing Cmt Behavioursmentioning
confidence: 99%